JOGOS PEDAGÓGICOS: UM RECURSO DIDÁTICO PARA A APRENDIZAGEM DE CIÊNCIAS E MATEMÁTICA NA EDUCAÇÃO INCLUSIVA PARA O ENSINO FUNDAMENTAL – ANOS FINAIS - Venturini, Andressa (2021)
This work is linked to the line of research Teaching and Learning in Science and Mathematics of the Postgraduate Program in Teaching Science and Mathematics - Professional Master's Degree, from the Franciscan University, and presents the title “Pedagogical Games: a didactic resource for the learning of Science and Mathematics in Inclusive Education for Elementary Education – Final Years”. It aims to develop a didactic resource, in the form of pedagogical games, directed to the teaching of Science and Mathematics in Inclusive Education, contemplating the general competencies of the Common National Curricular Base for Elementary Education - Final Years. This study had as reference the Common National Curricular Base (BRASIL, 2017), focusing on the interdisciplinarity of Inclusive Education. The target audience was students with Disabilities and / or with Specific Learning Difficulties, enrolled at the Alfredo Schlesner Municipal Elementary School - Specialized Educational Center, in the Municipality of Paraíso do Sul, Rio Grande do Sul, Brazil. Research with qualitative aspects was carried out and pedagogical games were produced as a didactic resource. The games produced were: Division Trail, Roulette of Numbers, Tangram of Birds and Battle of Words. A didactic sequence for the application of the games was used as a teaching strategy. The application of the four educational products in the school provided opportunities for the four students to learn, who showed interest and motivation in the development and resolution of the game. Everyone liked to participate in this proposal at school, including replicating the didactic material at home and inviting family members to explore the game. It has been proven that pedagogical games bring benefits to the teaching and learning process of students with Specific Learning Difficulties.